The role of ketogenic diet in an infant with intractable neonatal seizures : a case report. - Mohd Fakharuddin, Mohd Feizel Alsiddiq; J., Irne; U., Noriati
The ketogenic diet is a high fat, adequate- protein, low carbohydrate diet that helps to reduce seizures in patient with epilepsy. PNM is a 4 month old Malay girl, diagnosed with intractable neonatal epilepsy since day 7 of life. She was 5.6 kg and has 62 cm of body length during admission. Estimated calorie requirement was 742 kcal with 12.8g protein per day. Initially, the baby was fed by her mother through bottle and ryle’s tube on standard infant formula with added fat supplement. The ketogenic diet was started with a 2:1 ratio of fat to non-fat consisting of standard infant formula with addition of fat and carbohydrate supplements. This initial diet was not tolerated well; patient had diarrhea and persisting seizures. Finally, a ketogenic formula with a 4:1 fat to non-fat ratio was prescribed which provides 657 kcal with 13.7g protein per day and improved patient’s condition tremendously. On discharge, PNM had gained weight (5.74 kg) and no longer had any seizures. In conclusion, ketogenic diet is recommended to help improve seizures among patients with epilepsy.